Cisplatin and doxorubicin induce distinct mechanisms of ovarian follicle loss; imatinib provides selective protection only against cisplatin. - Stephanie Morgan; Federica Lopes; Charlie Gourley; Richard A Anderson; Norah Spears (PLoS ONE)
Purpose Chemotherapy treatment in premenopausal women has been linked to ovarian follicle loss and premature ovarian failure; the exact mechanism by which this occurs is uncertain. Here, two commonly used chemotherapeutic agents (cisplatin and doxorubicin) were added to a mouse ovary culture system, to compare the sequence of events that leads to germ cell loss. The ability of imatinib mesylate to protect the ovary against cisplatin or doxorubicin-induced ovarian damage was also examined. Experimental design Newborn mouse ovaries were cultured for a total of six days, exposed to a chemotherapeutic agent on the second day: this allowed for the examination of the earliest stages of follicle development. Cleaved PARP and TUNEL were used to assess apoptosis following drug treatment. Imatinib was added to cultures with cisplatin and doxorubicin to determine any protective effect. Results Histological analysis of ovaries treated with cisplatin showed oocyte-specific damage; in comparison doxorubicin preferentially caused damage to the granulosa cells. Cleaved PARP expression significantly increased for cisplatin (16 fold, p<0.001) and doxorubicin (3 fold, p<0.01). TUNEL staining gave little evidence of primordial follicle damage with either drug. Imatinib had a significant protective effect against cisplatin-induced follicle damage (p<0.01) but not against doxorubicin treatment. Conclusion Cisplatin and doxorubicin both induced ovarian damage, but in a markedly different pattern, with imatinib protecting the ovary against damage by cisplatin but not doxorubicin. Any treatment designed to block the effects of chemotherapeutic agents on the ovary may need to be specific to the drug(s) the patient is exposed to.